THU0125 Prednisolone Causes Dose Related Unfavourable Effects on Body Composition in Early Rheumatoid Arthritis Patients During the First Year of Treatment. (9th June 2015) - Konijn, N.; van Tuyl, L.; Den Uijl, D.; Ter Wee, M.; Kerstens, P.; Voskuyl, A.; van Schaardenburg, D.; Lems, W.; Nurmohamed, M.
Abstract : Background: Prednisolone improves disease activity in rheumatoid arthritis (RA), but is also associated with cardiovascular side effects and may negatively influence body composition. Rheumatoid cachexia (i.e. loss of lean mass and gain in fat mass) is often observed in chronic RA patients, with deleterious effects on morbidity and functional capacity [1, 2]. Objectives: To investigate the effect of two different prednisolone regimens on body composition in early RA patients in a 1 year randomized trial. Methods: The trial included 164 active RA patients who were randomised to either COBRA therapy (prednisolone starting at 60 mg/day tapered to 7.5 mg/day in 6 weeks, MTX 7.5 mg/week and sulfasalazine 2 g/day; n=81) or COBRA light therapy (prednisolone starting at 30 mg/day tapered to 7.5 mg/day in 9 weeks and MTX escalated to 25 mg/week in 9 weeks; n=83) [3, 4]. In an add-on study 36 resp. 39 patients underwent whole body DXA scans within 4 weeks ($≈ $baseline), 26 and 52 weeks after start of treatment. Results: Mean age was 52 years and 64% was female. Mean prednisolone use during first year of treatment was 2500 mg in the COBRA group and 2182 mg in the COBRA-light group. Both treatment groups showed significant increases in body mass index (BMI), body weight and fat mass after 26 and 52 weeks of treatment (Table 1 ). In GEE analysis, increases in cumulative prednisolone dose were significantly associated with increases in all body composition parameters (all individual models: p<0.05, independent of DAS). Conclusions: Initial high-dose prednisolone causes partially reversible, dose-related increases in BMI and body weight in early RA patients during the first year of treatment. Fat mass increased in both treatment groups. These increases are unfavourable from a cardiovasculair point of view. References: Walsmith & Roubenhoff, Int J Cardiol 2002. Konijn et al, Scand J Rheumatol 2014. Den Uyl et al, Ann Rheum Dis 2013. Ter Wee et al, Ann Rheum Dis 2014. Disclosure of Interest: N. Konijn: None declared, L. van Tuyl: None declared, D. Den Uijl: None declared, M. Ter Wee: None declared, P. Kerstens: None declared, A. Voskuyl: None declared, D. van Schaardenburg: None declared, W. Lems: None declared, M. Nurmohamed Grant/research support from: This research was performed within the framework of project T1-106 of the Dutch Top Institute Pharma, and was additionally funded by an unrestricted grant from Pfizer